Determinants of market participation among small scale shea butter processors in Kwara State, Nigeria (2018)
The fact that shea butter is gaining much importance in the international market coupled with the high demands from confectionery and cosmetic industries call for empirical analysis on market decision among processors. The study examined the factors that inform market participation decision in shea butter among small scale processors in Kwara state. Zones A and C were purposively selected from the four ADP zones in Kwara State due to preponderance of Shea butter marketing activities. Simple random sampling was used to select 118 respondents. Data were collected through the use of interview schedule on the socio- economic characteristics of respondents, shea butter market participation and constraints to shea butter market participation. It was revealed the average age of the respondents was 33 years, most were married (92.4%), illiterate (55.4%), lacked access to credit and market information with average income of ₦233, 547.06 (US$ 659.23) per annum. Lack of storage facility (x̅ =2.12), distance to market ( x̅ =2.10) and discrimination from buyer (x̅ =2.00) were major constraints to shea butter marketing. Age (β=-0.29), educational qualification (β=0.17), proximity to market (β=-0.22), access to market information (β=0.30), production output (β=0.34) and income (β=0.007, 0.026) from shea butter including membership in a group (β=1.39) significantly influenced respondents’ decision to participate in shea butter marketing. The study concludes that shea butter processors in the study area have potential to contribute to economic growth and development but lack full participation in large scale or international markets thus, relying mostly on small local community based markets. Hence, it is recommended that shea butter processors be sensitised on investment of external incomes into shea butter production as a profitable venture and policy makers should also promote the village market collection centers.